2023
DOI: 10.3390/metabo13030320
|View full text |Cite
|
Sign up to set email alerts
|

NMR Metabolomics and DNA Sequencing of Escherichia coli and Staphylococcus aureus Cultures Treated with Hydrolyzable Tannins

Abstract: Escherichia coli and Staphylococcus aureus are globally among the most prominent bacterial strains associated with antibacterial resistance-caused deaths. Naturally occurring polyphenols, such as hydrolyzable tannins, have been shown to potently inhibit E. coli and S. aureus. The current study investigated the metabolome changes of E. coli and S. aureus cultures after treatments with different hydrolyzable tannins using an NMR metabolomics approach. Additionally, the effect of these tannin treatments influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It has been reported that tellimagrandin I on MRSA acts on penicillin-binding protein 2a (PBP2a) decreasing its production and inactivating it [56]. PBP is a protein enables resistance to β-lactam antibiotic drugs in MRSA, PBP2a is encoded by the mecA gene found in MRSA strains, which gives resistance to betalactam antibiotics due to its low affinity for them, and PBP2a provides transpeptidase activity to allow cell wall synthesis at concentrations that inhibit the sensitive PBPs normally produced by S. aureus [57]. Likewise, in E. coli, the characteristics of the free galloyl groups of the ellagitannins increase the hydrophobicity of the structure, promoting their interaction with bacterial lipid membranes [58], through inactivation of essential surface proteins, interaction with membrane lipids and causing membrane phase separation [59].…”
Section: Effect Of Tellimagrandin I On Pathogenic Bacteriamentioning
confidence: 99%
“…It has been reported that tellimagrandin I on MRSA acts on penicillin-binding protein 2a (PBP2a) decreasing its production and inactivating it [56]. PBP is a protein enables resistance to β-lactam antibiotic drugs in MRSA, PBP2a is encoded by the mecA gene found in MRSA strains, which gives resistance to betalactam antibiotics due to its low affinity for them, and PBP2a provides transpeptidase activity to allow cell wall synthesis at concentrations that inhibit the sensitive PBPs normally produced by S. aureus [57]. Likewise, in E. coli, the characteristics of the free galloyl groups of the ellagitannins increase the hydrophobicity of the structure, promoting their interaction with bacterial lipid membranes [58], through inactivation of essential surface proteins, interaction with membrane lipids and causing membrane phase separation [59].…”
Section: Effect Of Tellimagrandin I On Pathogenic Bacteriamentioning
confidence: 99%
“…From these, PAs and HTs possess large structural variability; PAs are oligo- and polymers formed of two or multiple flavan-3-ol units, while HTs are a diverse class of monomeric and oligomeric polyphenols with monomeric units consisting of a cyclic or acyclic polyol at their center furnished with a variable number of esterified variants of galloyl groups [ 2 ]. PAs and HTs have been shown to possess a number of different bioactivities, such as antioxidant [ 3 , 4 , 5 ], antimicrobial [ 6 , 7 , 8 ], and antiparasitic [ 9 , 10 , 11 , 12 , 13 ] activities. They have also been proven to produce a number of beneficial effects on ruminants when added to animal feed, including reduced greenhouse gas emissions and increased milk production [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%